2020
DOI: 10.7759/cureus.9183
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Vertebral Artery Dissection Is an Under-Recognized Cause of Stroke in Young Patients: Two Case Reports and Review

Abstract: Cervicocerebral artery dissection (CAD) is an important and under-recognized cause of strokes in young and middle-aged patients. Spontaneous vertebral artery dissection (VAD) is a rare condition that can potentially cause a stroke without any preceding trauma or other causes of dissection. VAD rarely simulates classical headache syndromes. In this report, we discuss two young patients who were initially misdiagnosed as cases of headache until they presented with ischemic events, and were eventually diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pain is often a frequent preceding symptom, especially in traumatic dissections, and in spontaneous dissections, it can be delayed for hours to days [ 7 ]. It is usually characterized as severe, dull, and non-throbbing and generally localized in the upper portion of the neck and occiput, ipsilateral to the side of the dissection [ 8 ]. In our case, the patient presented with generalized neck pain, which many physicians misinterpret as musculoskeletal in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is often a frequent preceding symptom, especially in traumatic dissections, and in spontaneous dissections, it can be delayed for hours to days [ 7 ]. It is usually characterized as severe, dull, and non-throbbing and generally localized in the upper portion of the neck and occiput, ipsilateral to the side of the dissection [ 8 ]. In our case, the patient presented with generalized neck pain, which many physicians misinterpret as musculoskeletal in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Although spontaneous VAD could be considered, it is also possible that connective tissue diseases, such as Ehlers−Danlos syndrome, which can lead to vascular fragility, may be the cause of this VAD and should be investigated genetically. 13 , 16) In approximately 90% of cases, 17 , 18) the VA runs steeply into the transverse foramen at the level of the C6 vertebra and is prone to be injured by external forces such as flexion or rotation. 12) Even in cases where it is presumed to be spontaneous VAD, there is a certain number of cases that have been preceded by minor trauma such as various sports-related injuries, stretching, or severe coughing.…”
Section: Discussionmentioning
confidence: 99%
“…12) Even in cases where it is presumed to be spontaneous VAD, there is a certain number of cases that have been preceded by minor trauma such as various sports-related injuries, stretching, or severe coughing. 16) Additionally, the connection point between the longitudinal dorsal artery and the seventh cervical segmental artery during the embryonic development process [17][18][19] could lead to dissection due to its potentially histological fragility. 20) Furthermore, in this case, convulsion and apnea required intratracheal intubation, which delayed the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed 11 research papers comprising a total of 4,840 patients. From these finalised studies, we identified two case-control studies [ 2 , 5 ], three case reports [ 6 , 13 , 14 ], three narrative reviews [ 3 , 4 , 9 ], one retrospective observational study [ 1 ], one cohort study [ 12 ], and one experimental study [ 15 ]. All the studies include young patients presenting to the hospital with either TIA or stroke, evaluated to identify HHCY and further MTHFR gene C677T polymorphism, or patients with cervical/vertebral artery dissections, presenting with cervicogenic headache, which were often initially misdiagnosed as migraine with aura, until later returning with more serious outcomes.…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, HCY may contribute to the onset of migraines by generating superoxide anions, leading to oxidative damage to the vascular endothelium and hence this forms the primary presenting complaint of most individuals [ 4 , 21 ]. Elkady et al, in their case studies, concluded that presentations of CAD and VAD are frequently subject to misdiagnosis, and diagnosis is often delayed until ischemic events occur [ 13 ]. They observed that genetic connective tissue conditions, migraine with aura, hypertension, HHCY, and a recent history of infections were reported more frequently in patients with VAD compared to healthy controls.…”
Section: Reviewmentioning
confidence: 99%